Influence of root curvature’s initial position on apical deviation occurrence after oscillatory preparation in simulated root canals - Tiago André Fontoura de Melo; Luciana Dellinghausen Silveira; Vanessa Santos Simões Pires; Simone Viegas da Silva; Luis Eduardo Duarte Irala (Revista Sul-Brasileira de Odontologia, 2012)
Introduction and objective: This study aimed to analyze the influence of root curvature’s initial position on apical deviation occurrence after oscillatory system preparation. Material and methods: For this purpose, we used twenty simulated root canals with 21 mm length and 30 degree angle, which were divided into two experimental groups according to curvature’s initial position: 8 mm (group A) and 12 mm (group B) short of the canal orifice. The canals were prepared using crown-down technique, and memory instrument was size #30. For apical deviation analysis, before and after preparation, canals were filled with Indian ink and standardly photographed with the aid of a platform. After that, the images were manipulated by Adobe Photoshop® software, through superimposing pre- and post-operative images. Deviation occurrence was measured 1 mm short of working length and at the middle of the curvature by using the ruler tool. Data were subjected to analysis of variance (ANOVA) with significance level set at 5%. Results: Although group B showed a significantly greater deviation mean than group A, no significant interaction was verified between the analysis site and the experimental group. Conclusion: According to the present data, it could be observed that the smaller the curvature radius, the greater the deviation. Concerning to the analysis site, it could be noted that the area 1 mm short of working length presented a higher deviation than the point at the middle of the curvature.